2019
DOI: 10.1200/jco.2019.37.15_suppl.e12533
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib with or without fulvestrant for the treatment of hormone receptor-positive and HER2-negative metastatic breast cancer with disease progression following prior treatment with palbociclib.

Abstract: e12533 Background: Abemaciclib is a selective inhibitor of CDK4 and CDK6 kinase activity. It is approved for patients with hormone receptor (HR) positive, human epidermal growth factor receptor 2 (HER2) negative, advanced or metastatic breast cancer (MBC) previously treated: in combination with fulvestrant for patients with disease progression following endocrine therapy (MONARCH 2) and as monotherapy for patients with disease progression after endocrine therapy and chemotherapy for MBC (MONARCH 1). The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Six studies reported the median treatment duration for CDK4/6i (Supplementary Appendix 2) [49,52,[61][62][63][64]. The longest median treatment duration reported was 19 months for first-line ribociclib plus AI [49] and the shortest duration was 1.8 months for palbociclib plus AI across all lines of therapy (Table 3) [61].…”
Section: Treatment Durationmentioning
confidence: 99%
“…Six studies reported the median treatment duration for CDK4/6i (Supplementary Appendix 2) [49,52,[61][62][63][64]. The longest median treatment duration reported was 19 months for first-line ribociclib plus AI [49] and the shortest duration was 1.8 months for palbociclib plus AI across all lines of therapy (Table 3) [61].…”
Section: Treatment Durationmentioning
confidence: 99%
“…Since our patient maintained a good performance status and desired more therapy after four HT regimens, including letrozole and palbociclib, and more than five chemotherapy regimens, it seemed reasonable to try abemaciclib due to lack of other good options and a significant interval since prior exposure to a CDK4/6 inhibitor. Since the patient started this therapy, additional data emerged from multiple institutions indicating activity of abemaciclib after failure of palbociclib in a prior line of therapy [12][13][14][15] as summarized in Table 2. The purpose of this report is to raise awareness about this option and to allude to this lack of complete cross-resistance between the two CDK4/6 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of pts derived clinical benefit with continued exposure to CDK4/6i Wander et al 2019 [ 13 ] Evaluated clinical outcomes in pts with HR+/HER2− MBC who received abemaciclib following progression on prior palbociclib at four US academic centers Twenty-one pts (36%) had abemaciclib treatment duration exceeding 6 months (alone or combined), including 10 who remained on treatment at interim analysis (range 181–413 days). This is the first multi-center experience demonstrating a substantial proportion of pts with clinical benefit with abemaciclib after prior CDK4/6i exposure Tamragouri et al 2019 [ 14 ] Performed a chart review of pts with HR+, HER2− MBC who progressed on palbociclib and were subsequently treated with abemaciclib with or without fulvestrant Twenty-one pts were included. The clinical benefit rate for using abemaciclib after previous exposure to palbociclib was 29% (6/21).…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter analysis of 58 MLBC patients receiving abemaciclib as monotherapy or in combination with endocrine treatment after progression on palbociclib suggested some clinical benefit based on a median PFS of 5.8 months and a treatment duration of 6 months or longer in one third of the patients [39]. Two further retrospective analyses of small patient cohorts receiving abemaciclib as a monotherapy [40] or in combination with endocrine therapy [41] in the same clinical setting seem to confirm a limited clinical activity of abemaciclib beyond CDK4/6i progression, with a median PFS up to 7.0 months. Continuation of palbociclib beyond progression, while switching the endocrine therapy, was evaluated in a small, retrospective, single-institution study [42].…”
Section: Cdk4/6i Beyond Progressionmentioning
confidence: 99%